Sensitization in transplantation: Assessment of risk (STAR) 2019 Working Group Meeting Report. Issue 10 (27th May 2020) - Tambur, Anat R.; Campbell, Patricia; Chong, Anita S.; Feng, Sandy; Ford, Mandy L.; Gebel, Howard; Gill, Ronald G.; Kelsoe, Garnett; Kosmoliaptsis, Vasilis; Mannon, Roslyn B.; Mengel, Michael; Reed, Elaine F.; et al.
Abstract : The purpose of the STAR 2019 Working Group was to build on findings from the initial STAR report to further clarify the expectations, limitations, perceptions, and utility of alloimmune assays that are currently in use or in development for risk assessment in the setting of organ transplantation. The goal was to determine the precision and clinical feasibility/utility of such assays in evaluating both memory and primary alloimmune risks. The process included a critical review of biologically driven, state‐of‐the‐art, clinical diagnostics literature by experts in the field and an open public forum in a face‐to‐face meeting to promote broader engagement of the American Society of Transplantation and American Society of Histocompatibility and Immunogenetics membership. This report summarizes the literature review and the workshop discussions. Specifically, it highlights (1) available assays to evaluate the attributes of HLA antibodies and their utility both as clinical diagnostics and as research tools to evaluate the effector mechanisms driving rejection; (2) potential assays to assess the presence of alloimmune T and B cell memory; and (3) progress in the development of HLA molecular mismatch computational scores as a potential prognostic biomarker for primary alloimmunity and its application in research trial design. Abstract : This meeting report from an AST‐ASHI expert workgroup provides recommendations on the utility and "clinical‐grade" qualification of assays and biomarkers to evaluate alloimmune risk.